Social Network Analysis: E-Marketing Sales of “Kue Lebaran” in the Perspective of the Technology Acceptance Model - Sitti Hardiyanti Arhas; Risma Niswaty; Tri Cahyono; Nawir Rahman (Pinisi Business Administration Review, 2022)
E-marketing creates fundamental changes in business and consumer behavior, this happens because marketing does not require a lot of money, in contrast to traditional marketing. The purpose of this study was to determine e-marketing in selling Eid cakes (kue lebaran) from the perspective of the Technology Acceptance Model by using Social Network Analysis. The data is obtained from tweets on the Twitter application, the data obtained are tweets from April 2-20 2022. Data analysis uses the ATLAS.ti application. This study uses the keyword "jual kue lebaran", including only tweets, without retweets and images. Meanwhile Create codings from: authors, mentions, hashtags, and query hashtags only. Then do network analysis, tweets that stand alone or have no relationship with other tweets will be eliminated or excluded. Based on the results of data analysis, it was found that Eid cake producers on the Twitter market their sales in the form of general promotional tweets or mentions to several accounts using easy word selection in conducting searches.